ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA PEGAWAI BPBD KABUPATEN HULU SUNGAI UTARA - Parnami Azmi (Politeknik Bisnis Indonesia, 2023)
This study aims to analyze the effect of workload, facilities and motivation on the performance of BPBD employees in Hulu Sungai Utara. Quantitative research methods can be interpreted as research methods based on the philosophy of positivism, used to examine certain populations or samples. The population in this study were all BPBD employees of Hulu Sungai Utara, 42 people. All members are taken as a sample is called saturated sampling or another term is a census. So the number of samples in this study were 42 people. The analysis technique used is multiple linear regression analysis with SPSS 23.0 for windows. The results of the study show that workload has an effect on the performance of BPBD employees in Hulu Sungai Utara Regency. Facilities affect the performance of BPBD employees in Hulu Sungai Utara Regency. Motivation influences the performance of BPBD employees in Hulu Sungai Utara Regency. Workload, facilities and motivation simultaneously influence BPBD employee performance in Hulu Sungai Utara Regency.